STRATEGI PEMANFAATAN MEDIA SOSIAL DAN APLIKASI ANTAR MAKANAN BAGI UMKM DI SALATIGA PADA MASA PANDEMI COVID 19 - Tri Widodo; Elisa Irawati; Dicky Irvan Nauval (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
ABSTRACT The Covid-19 pandemic has hit the world, dragging countries into a slump. The impact is not only on the world of health but also spreads to economic problems. The policy of social or physical distancing is an external factor everyone must obey. This study aimed to determine the role of social media and food delivery applications for MSMEs in Salatiga and how MSMEs appropriately determine social media and food delivery applications. This study uses a qualitative method with a phenomenological approach. This research was conducted in Salatiga City, Central Java, with the object of culinary business SMEs utilizing social media and food delivery applications as a strategy in increasing their marketing during the COVID-19 pandemic. Research findings: By using social media and food delivery applications, MSMEs can increase the number of customers, expand market coverage, have promotional media, earn income, save time, improve service quality and increase credibility. The use of social media and food delivery applications, both by application and non-application, has become a necessity for SMEs in Salatiga and consumers.